PENGARUH MODEL MAKE A MATCH BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA PESERTA DIDIK KELAS V SD - Ayu Nurjanah, Nadia; Pangestu, Deviyanti; Abung, Miranda; Erni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem of this research is the low learning outcomes of Pancasila Education for fifth-grade students at SDN 5 Metro Pusat, due to the lack of variety of learning models and learning media applied. This research aimed to improve the learning outcomes of fifth-grade students in elementary school in the subject of Pancasila Education by using make a match model assisted by puzzle media. This study employed a quantitative research approach using an experimental method and a non-equivalent control group design. The population in the study is all students of fifth-grade of SDN 5 Metro Pusat, totaling 55 students. The sampling technique employed in this study was non-probability sampling using total sampling, in which 28 students from class VA were assigned as the experimental group and 27 students in the control class. The data collection technique in the form of achievement tests, observation, and documentation. Based on the results of the study, it can be concluded that there is an influence and significant difference from the use of the make a match model assisted by puzzle media on learning outcomes in Pancasila education subjects for fifth-grade students at SDN 5 Metro Pusat academic year 2025/2026.